Friends of foes? Case of arising financial technology in financial industry - Chua, Lui Eeh; Gan, Zhi An; Lim, Wan Ting; Lew, Esther Shu Xin; Wong, Zhi Ying (2020)
The objective of this research is to investigate and provide in-depth understanding on how the financial technology (FinTech) influencing the financial industry in the United States of America (USA). Furthermore, this research examines how the internal factor, which is Bank Size as well as macroeconomic factors comprises of Foreign Direct Investment (FDI), Gross Domestic Product (GDP) and Inflation brings impact to the dependent variable used in this research, Return on Assets (ROA). In addition, the relationship between exogeneous and endogenous variables are observed. Moreover, quarterly time series data from year 2012 was applied in this study by consisted total of 32 observations. To mark the results, E-View was used and several tests such as Bound Test, Cointegration test, Vector Error Correction Model (VECM) and others related test method were applied in this research. From the outcome generated, it shows that FinTech, Bank Size, FDI and GDP have significant relationship to ROA except for Inflation. However, all the variables do not have significant relationship to ROA when it comes to short run relationship. Nevertheless, limitation and recommendation had discussed in Chapter 5 to provide some useful hints for future researcher who are interested in relevant topic.